Charged aerosol detection for liquid chromatography and related separation techniques - Gamache, Paul H., 1957- (John Wiley & Sons, Inc., 2017)
Using numerous real-world examples, this timely and authoritative book presents a comprehensive review of CAD theory, describes its advantages and limitations, and offers extremely well-informed recommendations for its practical use. -- Edited summary from book.
Keywords: Liquid chromatography.; Atmospheric aerosols.; Aerosols.; Electrostatic precipitation.; Separation (Technology); elektronické knihy; electronic books